Implementasi Sistem Otomatisasi Internet of Things Sebagai Penghematan Energi Listrik Pada Lampu LED-14 Base On Mikrokontroler ESP8266 (NodeMCU) Dan Bot. Telegram Di Perumahan Griya Sutera Balaraja - Ade Sumaedi; Angelina Hadriani; Agus Suhendi (Faktor Exacta, 2025)
Increasing electrical energy efficiency has become one of the primary focuses in current technological development. This research aims to design and implement an Internet of Things (IoT)-based automation system to reduce electricity consumption for LED-14 lamps in Perumahan Griya Sutera Balaraja. The system integrates ESP8266 (NodeMCU) microcontroller with Android applications and Telegram bot as remote communication and control platforms. Through the Android application and Telegram bot, users can control and monitor the lamp status in real-time, enabling more effective energy savings and responsiveness to user needs. The author leverages internet/Wi-Fi advancements and the Android system to create a system that is quick, precise, and accessible from anywhere, at any time. The development of the automation design for On/Off LED-14 lighting based on Internet of Things (IoT) simplifies human activities. The research method begins with designing the physical form or Hardware System using NodeMCU 8266 microcontroller connected to the internet network using Arduino IDE programming software. The design results demonstrate significant reduction in electricity consumption by ensuring lamps are only lit when needed. Moreover, integration with Telegram bot facilitates ease of control and monitoring, making this system an effective and efficient solution in managing electricity usage.